High-risk human papillomavirus infection and associated factors in the anal canal of HIV-positive patients in Medellín, 2017-2018 - Daniela Herrera Posada; Lucia Stella Tamayo Acevedo; Marleny Valencia Arredondo; Gloria Inéz Sánchez Vásquez (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE To estimate the prevalence of high-risk human papillomavirus (HR-HPV) anal infection and associated factors in human immunodeficiency virus (HIV) positive patients in Medellín. METHODS Descriptive cross-sectional study in 300 HIV-positive patients, adults, with history of anal intercourse, treated in two health care services of Medellín 2017-2018. We conducted a structured survey on sociodemographics, sexual behavior and medical history. HPV was detected in anal swabs tested by the COBAS 4800 system. Exploratory data analysis of risk factors associated with HR-HPV was conducted by chi-square test of independence and both raw and adjusted prevalence ratios used the Poisson regression model, at a 95% confidence interval. RESULTS The high-risk HPV had a prevalence of 82.7%; HPV16 had a prevalence of 32.7%, HPV18 a prevalence of 21.7% and other HPV types scored 78.3%. The high-risk HPV prevalence in women was of 68.2% and 83.8% in men. The risk factors associated with high-risk HPV after adjustment were age under 30 years, elementary education, casual sex partners, and first sexual activity before 18 years old. CONCLUSIONS The high incidence of high-risk HPV, along with the occurrence of coinfections by multiple types in the study population shows their susceptibility to develop some type of anal intra-epithelial neoplasia. It is important to establish sexual health programs focused on primary health care.